Effects of papersludge ashes in cement - Larsson, Kristian (My University, 2007)
Historically, ash was added to lime to create hydraulic materials. In modern cement primarily coal fly ashes have been used which influences the chemical and physical properties of cement and has economical and environmental benefits. However there are other ashes than coal fly ashes that can have beneficial properties. In this work two ashes from the paper-industry were investigated to examine their influences on the properties of portland cement. The influence of silica sol in combination with the ashes was also investigated by the use of Cembinder 50 from Eka Chemicals AB. The ashes and the used cement were characterized through SEM, XRD, DR-FTIR, BET, particle size and Vicat measurements. The ashes were then added to cement mixes by 10\% or 30\% to the solid weight, with or without the addition of silica sol. The early hydration period of the mixtures was evaluated by preparing samples with a freeze drying method and then performing DR-FTIR measurements on these. The method to prepare the samples by freeze drying was developed in order to be able to produce ''snap-shot'' images of the chemical properties of the paste. XRD-measurements were made in order to examine the change in composition in the mixtures. To evaluate the structure and phases in the samples a scanning electron microscope (SEM) was used. The setting times of the different mixtures were examined through the use of Vicat measurements. The ashes were found to influence the settingtime and composition of the cement due to the differences in phases and chemical composition. One of the ashes was found to have a greater abundance of glassy particles and it had a self-cementitious ability. The silica affected the properties of the cement mixtures, lowering the settingtimes, except for one mixture that had a very fast settingtime. For this mixture the settingtime was lengthened by the silica sol addition. The ashes had a clear influence on the cement chemistry which was shown by the DR-FTIR measurements.
Keywords: Oorganisk kemi; Inorganic Chemistry